The Process of Evaluation of Performance in the Civil Service: A Comparative Analysis of the Legal to the Practice of Performance Evaluators in the District Government of Nacar (London Journal of Research In Humanities and Social Sciences, 2023)
Our scientific research has as its theme “The performance evaluation process in the civil service: a comparative analysis of the legal to the practice of performance evaluators in the district government of Nacarôa” aims to analyze the perceptions that performance evaluators in District Government of Nacarôa have on the performance evaluation process in the civil service. Asfor the approach, the research is qualitative, using the case study. The interview was the technique used for data collection, whose analysis and interpretation was based on content analysis, based on pre-defined categories. The sample consists of performance evaluators from five public institutions.The survey results indicate that the monitoring of the annual activity plan is the means that performance evaluators use to communicate and control the execution of activities, according to the priorities defined by each sector or division, in compliance with article 21 of the SIGEDAP, which establishes the following duties of evaluators: communicating the objectives, policies, strategies and plans of the body or institution to the person being evaluated; monitor and guide the person being evaluated during the execution of the activities; evaluate performance in good faith, fairly, impartially, accountability, transparency and impartiality; that the evaluation process, in the five institutions, is effective when compared to the legal provision, as the evaluators monitor the degree of fulfilment of plans and goals, maintaining a permanent dialogue between the parties until the final stage of the performance evaluation that is carried out through interviews, with a view to ensuring an effective management of human resources in the Public Administration.
Keywords: public service; performance evaluation; communication; responsibility